2007
DOI: 10.1007/s11604-007-0128-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of breast cancer detection by diffusion-weighted magnetic resonance imaging and mammography

Abstract: DW-MRI may be useful for detecting breast cancer in a wide age group of women, including young women with dense mammary glands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
3
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 15 publications
3
49
3
1
Order By: Relevance
“…In a study by Choi et al (30) /sec and the mean ADC value of 6 DCIS lesions was 1.305x10 -3 mm 2 /sec when the b value was 1000. The reasons for this difference were that invasive ductal carcinoma is a type of cancer that is heavier with cells and it restricts water diffusion more compared with DCIS (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Choi et al (30) /sec and the mean ADC value of 6 DCIS lesions was 1.305x10 -3 mm 2 /sec when the b value was 1000. The reasons for this difference were that invasive ductal carcinoma is a type of cancer that is heavier with cells and it restricts water diffusion more compared with DCIS (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…One study (46) conducted a cost-effective analysis regarding WB-MRI. They concluded that substantial savings are achievable with the use of WB-MRI for preoperative tumor staging.…”
Section: Discussionmentioning
confidence: 99%
“…The principle of the DWI is related to the Brownian movement of the water particles, which is restricted due to structure of the environment depending on the cellularity degree of the lesions (18,19). The apparent diffusion coefficient (ADC) value as a quantitative measurement of diffusion has been observed by several studies to further help lesion characterization and discrimination when evaluated along with DCE-MRI (20)(21)(22).…”
mentioning
confidence: 99%